The Relationship Of Motivation, Work Environment, Work Discipline And Job Satisfaction To Employee Performance In The Health Department Of East Kalimantan Province In 2023 - Putri, Tiara; Gunawan, Ike Anggraeni; Wisnuwardani, Ratih Wirapuspita (Faculty of Public Health Mulawarman University, Indonesia, 2025)
Background : The success of an organization cannot be separated from the improvement of human resources, human power must always be managed so that superior and quality resources are formed, Employee Performance can be influenced by factors of Motivation, Work Environment, Work Discipline and job satisfaction. One of the organizations in East Kalimantan is the East Kalimantan Provincial Health Office which is an implementing element of the Provincial Government, at the East Kalimantan Provincial Health Office, it is known that there are 8 performance indicators, some of which have decreased. Objective : This study aims to determine the relationship between motivation, work environment, work discipline and job satisfaction on employee performance at the East Kalimantan Provincial Health Office, This research design is cross-sectional, with a population of East Kalimantan Provincial Health Office employees. Research Methods/ Implementation Methods : The sample of this study was 80 employees of the East Kalimantan Provincial Health Office who had ASN status (Total Sampling). The instrument used in this study was a questionnaire. Statistical tests using the Chi-Square test. Results : The results of bivariate analysis in this study showed that there was a relationship between job satisfaction and employee performance (□=0.003), on the Motivation variable no relationship was found with employee performance (□=0.712), on the work environment variable also found no relationship with employee performance (□=0.777), as well as the work discipline variable found no relationship with employee performance (□=0.777). Conclusion/Lesson Learned : There is a relationship between job satisfaction and employee performance, there is no relationship between motivation, work environment and work discipline on employee performance. it is recommended for the office to continue to improve employee performance for researchers to further research with other variables or in different locations.